2014
DOI: 10.1111/pce.12388
|View full text |Cite
|
Sign up to set email alerts
|

PHYTOALEXIN DEFICIENT4 affects reactive oxygen species metabolism, cell wall and wood properties in hybrid aspen (Populus tremulaL. × tremuloides)

Abstract: The phytoalexin deficient 4 (PAD4) gene in Arabidopsis thaliana (AtPAD4) is involved in the regulation of plant--pathogen interactions. The role of PAD4 in woody plants is not known; therefore, we characterized its function in hybrid aspen and its role in reactive oxygen species (ROS)-dependent signalling and wood development. Three independent transgenic lines with different suppression levels of poplar PAD expression were generated. All these lines displayed deregulated ROS metabolism, which was manifested b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 51 publications
0
14
0
Order By: Relevance
“…Furthermore, LSD1 is a condition‐dependent scaffold protein and transcription regulator, and forms dimers with EDS1 (Czarnocka et al ). Recently, we reported that PAD4 and EDS1 can function in woody plants in a similar manner as in Arabidopsis (Ślesak et al , Szechyńska‐Hebda et al , Bernacki et al ).…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…Furthermore, LSD1 is a condition‐dependent scaffold protein and transcription regulator, and forms dimers with EDS1 (Czarnocka et al ). Recently, we reported that PAD4 and EDS1 can function in woody plants in a similar manner as in Arabidopsis (Ślesak et al , Szechyńska‐Hebda et al , Bernacki et al ).…”
Section: Introductionmentioning
confidence: 77%
“…Salicylic acid (SA) and reactive oxygen species (ROS), such as H 2 O 2 , are important signaling molecules that regulate CD, photosynthesis, WUE, stomatal conductance and cross‐tolerance processes (Desikan et al , Gechev and Hille , Ślesak et al , Wituszyńska et al , Wituszyńska et al , Szechyńska‐Hebda et al , Bernacki et al , Czarnocka and Karpiński ). They also play a vital role in plant development (Mittler et al , Gawroński et al ) and seed yield control (Abreu and Munné‐Bosch ).…”
Section: Introductionmentioning
confidence: 99%
“…EDS1 plays an important role during oxidative stress caused by the release of singlet oxygen 49 . And PAD4 also involves in the integrated regulation of ROS homoeostasis 50 . The pathogen B. dothidea causes cankers characterised by the collapse of cells and discoloured areas; these cankers alter cellular regulatory processes and increase the production of ROS.…”
Section: Discussionmentioning
confidence: 99%
“…2 has been established as references suggested (Lin and Dence 2012;Zhou et al 2012;Ślesak et al 2015), and lignin content of black liquor and washing effluent is presented in Table 5. As pulp consistency increased, lignin brought to the alkali recovery unit increased from 34.98 g/t to 88.43 g/t, which will favor the vapor production and economical efficiency for soda recovery technique.…”
Section: Determination Of Lignin In Black Liquor and Washing Effluentmentioning
confidence: 99%